Separation of crude plant extracts with high speed CCC for primary screening in drug discovery - Harris, Guy H. (2001)
High speed countercurrent chromatography (HSCCC) was used in a pre-fractionation pilot study to improve the quality of crude plant samples for primary screening in drug discovery efforts. The methanol extracts of sixty-four plant samples were (i) defatted, (ii) treated with poly-N-vinylpyrrolidone (PVP) for polyphenolic removal, and (iii) fractionated with a multilayer coil planet centrifuge. The ternary solvent system CH2Cl2:MeOH:H2O (5:6:4, v/v/v) was used based upon elution of known plant natural product standards with ranging polarities. Elution was carried out until a partition coefficient (K) of 1, followed by column contents extrusion to exploit stationary phase separation and to increase the polarity range of compounds, fractionated. Fractionation was found to be consistent for all separated extracts with respect to sample recovery, stationary phase fraction (Sf), and weight distribution by fraction number. Biological evaluation was conducted in 20 mechanism-based, in-vitro assays with an evaluation of biodata trends. Bioassay interfering agents such as polyphenolics and fatty acids were chromatographically localized and rapidly identified.